Unraveling the effects of environmental drivers and spatial structure on benthic species distribution patterns in Eurasian-Arctic seas (Barents, Kara and Laptev Seas) - Miriam L. S. Hansen; Dieter Piepenburg; Dmitrii Pantiukhin; Casper Kraan (Polar Biology, 2020)
In times of accelerating climate change, species are challenged to respond to rapidly shifting environmental settings. Yet, faunal distribution and composition are still scarcely known for remote and little explored seas, where observations are limited in number and mostly refer to local scales. Here, we present the first comprehensive study on Eurasian-Arctic macrobenthos that aims to unravel the relative influence of distinct spatial scales and environmental factors in determining their large-scale distribution and composition patterns. To consider the spatial structure of benthic distribution patterns in response to environmental forcing, we applied Moran’s eigenvector mapping (MEM) on a large dataset of 341 samples from the Barents, Kara and Laptev Seas taken between 1991 and 2014, with a total of 403 macrobenthic taxa (species or genera) that were present in ≥ 10 samples. MEM analysis revealed three spatial scales describing patterns within or beyond single seas (broad: ≥ 400 km, meso: 100–400 km, and small: ≤ 100 km). Each scale is associated with a characteristic benthic fauna and environmental drivers (broad: apparent oxygen utilization and phosphate, meso: distance-to-shoreline and temperature, small: organic carbon flux and distance-to-shoreline). Our results suggest that different environmental factors determine the variation of Eurasian-Arctic benthic community composition within the spatial scales considered and highlight the importance of considering the diverse spatial structure of species communities in marine ecosystems. This multiple-scale approach facilitates an enhanced understanding of the impact of climate-driven environmental changes that is necessary for developing appropriate management strategies for the conservation and sustainable utilization of Arctic marine systems.